Comparative analysis of interlimb asymmetry in a RSA Test in basketball players - Mancha-Triguero, D.; Gómez-Carmona, C. D.; García-Santos, D.; García-Rubio, J.; Ibáñez, S. J. (Journal of Human Sport & Exercise, 2019)
Due to the training processes, the athlete occasionally develops asymmetries between limbs which can cause a deficit in performance or even injury. Therefore, in this paper, 63 basketball players were analysed (U´14 n= 15; U´16 n= 25; U´18n=23) to know if they had asymmetries between limbs in the different sprints of a RSA test. To this end, each athlete performed a RSA test 5x14 metres and the analysis differentiated between laterality of the support either right or left. The results show that there are no significant differences between sprints performed based on the same laterality of the support. However, there are significant differences in the variables when the analysis is made comparing right versus left step cycles. The data show that the athletes are well trained and that the effort made does not affect the athlete when the analysis is carried out comparing the same laterality. However, there are differences when the analysis compares laterality. This may be due to the lack of bilateral work and to the predominance of one side over the other what, in short efforts, does not affect the final performance.